Promoting sustainability through governance of eco-city indicators: a multi-spatial perspective - Peng, Zhen; Ma, Yuanli; Cheshmehzangi, Ali; Deng, Wu (2020)
The purpose of this paper is to present a case study of the latest practice on urban sustainability in China, focusing on the breakdown of city-wide overall indicators to a more controllable spatial level—i.e. individual land plots and individual buildings. We argue the importance of decomposing the indicators to smaller scales by understanding underlying principles such as indicators and their integration in the process of urban governance, i.e. enhancing multi-level policy coordination as an important and effective approach for developing eco-cities. This can provide a common ground of argument to monitor the progress at multiple spatial levels and form a collective effort to move a city towards sustainability. The novelty of this study is to highlight the role of eco-city development at multiple spatial levels and through urban governance. The local government needs to mobilize various stakeholders involved in the urban development process by providing sustainability targets in a transparent way. A collective effort from various stakeholder groups might be formed by linking them to a set of unified but spatial level-based targets.